Seasonal human coronavirus NL63 epidemics in children in Guilin, China, reveal the emergence of a new subgenotype of HCoV-NL63 - Zhu, Renhe; Cao, Rundong; Wang, Lulu; Gong, Yue; Cheng, Qian; Long, Hu; Xia, Dong; Song, Qinqin; Xia, Zhiqiang; Liu, Mi; Du, HaiJun; Song, Juan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Seasonal human coronavirus NL63 (HCoV-NL63) is a commonly occurring virus associated with mild upper respiratory infections. This study documents a rare localized epidemic of HCoV-NL63-induced respiratory infections in pediatric patients in Guilin, China. Among the 83 HCoV-NL63-positive children hospitalized with acute respiratory infections, we identified three subgenotypes (C4, C3, and B). Notably, 21 of these cases exhibited a previously unreported subtype, C4. Analysis revealed a unique amino acid mutation (I507L) in the receptor-binding domain of the spiking protein of the C4 subtype, akin to the mutation observed in the previously reported C3 genotype. This shared mutation raises concerns about potential increases in viral transmissibility and pathogenicity. The findings of this study underscore the rapid mutation dynamics of HCoV-NL63, suggesting a possible enhancement in virulence and an elevated risk of epidemic transmission. This research contributes valuable insights into the evolving nature of HCoV-NL63 and its potential public health implications.